Toward More Accurate GIC Estimations in the Portuguese Power Network - Joana Alves Ribeiro; Fernando J. G. Pinheiro; Maria Alexandra Pais; Rute Santos; João Cardoso; Pedro Baltazar‐Soares; Fernando A. Monteiro Santos (Space Weather)
Abstract New geomagnetically induced current (GIC) computations for mainland Portugal include the entire power network, with network parameters and topology provided by the transmission grid operator for all the high voltage lines (150, 220, and 400 kV). The first 3D conductivity model for the west region of the Iberian Peninsula, based on 31 broadband magnetotelluric soundings, is used in calculations, revealing the effect of different crustal domains in GIC distribution. Geomagnetic field variations are taken from Coimbra or San Fernando magnetic observatories, according to the Nearest Neighbor method, and used together with surface impedance values predicted from the new conductivity model to calculate the induced electric field on a regular grid. The global distribution of GICs over the power network is characterized based on results derived for the eight most significant storms registered in the Iberia during solar cycle 24. Substations susceptible to the highest GICs are found near the transition between the granitic geotectonic unit of Central Iberian Zone and the Lusitanian Basin. A prototype of a Hall effect sensor has been installed at a substation and is active since the end of August 2021. In order to validate our GIC model, recent measurements are compared with simulations. GIC computation is prone to uncertainties from various sources, possibly contributing with different weights to the final error in computed values. Here, we evaluate the contribution of substation earthing resistance and nonuniqueness of the conductivity model to the final GIC uncertainties.